The effects of natural nano-sized clinoptilolite and Nigella sativa supplementation on blood glucose and lipid profile in rats with type 2 diabetes mellitus - Omidi, Hossein; Khorram, Sirous; Mesgari, Mehran; Asghari-Jafarabadi, Mohammad; Tarighat-Esfanjani, Ali (Progress in Nutrition, 2019)
Objectives: Hyperglycemia and hyperlipidemia have major roles in incidence or development of complications diabetes mellitus. Regarding side effects of diabetes treatment, patients seek natural, economical, and more effective treatments. In current study we investigated the effects of separate and concurrent supplementation of natural nano-sized clinoptilolite (NCLN) and Nigella sativa (NS) on blood glucose and lipid profile (LP) in high-fat-diet (HFD)/streptozotocin (STZ)-induced diabetic rats. Methods: In this experimental study, 42 male Wistar rats divided into two groups as diabetic and non-diabetic. Diabetic group fed with HFD for 1 month, and then injected intraperitoneal single dose STZ (35 mg/kg BW). After a week, oral glucose tolerance test and homeostatic model assessment of insulin resistance (HOMA-IR) test was carried out to confirm diabetes. Diabetic group was divided to 4 subgroups: (1) control (n=9), (2) NS 1g/kg (n=9), (3) NCLN 2%/food (n=9), (4) NS 1g/kg + NCLN 2%/food (n=9). At end 7th week, fasting blood glucose, triglyceride, total cholesterol, low density lipoprotein cholesterol and high density lipoprotein cholesterol were tested. Data analysis was performed using SPSS software version 16 and P